Vegetablefruit Ui/Ux Application Design Using Mobile-Based Figma - Pradana, Orisa Deva; Nugroho , Setiya; Primadewi, Ardhin (Universitas Muhammadiyah Yogyakarta, 2024)
Food sources that provide many benefits for the body are fruits and vegetables. Fruits and vegetables have good content in them such as vitamins, minerals and dietary fiber which are good for the body. Freshness in fruits and vegetables is very influential on the content in them. Conversely, reducing consumption of fruits and vegetables is the same as increasing the risk of disease, including reducing health. It was proven in 2017 when 3.9 million people died because the level of consumption of fruits and vegetables was low. To overcome this, an application design was created to make it easier for users to find fresh fruit or vegetables, namely Vegetable Fruit. This platform can help users view stock information on fruit or vegetables being sold. With this research, further research is needed on user experience using an online-based vegetable selling platform. In this way, it can be seen how the user experience is using the Platform so that it can be used as a new reference for startups making online applications. In this study, one of the methods to solve the problem, namely the Design Sprint. Based on the results of research on the UI/UX design of the VegetableFruit application, one of the methods used, called Design Sprint, can solve this problem. In the results of the UI/UX design research, the Vegetable Fruit application has discount features, light mode, and has many payment methods that can make it easier for users.